Fire & flood - Barber, Nicola (Hauppauge, N.Y : Barron's Educational Series, 1999)
Explains why and where fires and floods happen and their effect on human life.
"First published in Great Britain in 1999 by ticktock Publishing ... Hadlow, Kent"--Colophon.
Includes index.
Keywords: Fire; Floods